Overview of 254 mild cases of COVID-19 in Bangladeshi cohort: a cross-sectional observation - Zahan, Tahmina; Nasir, Morshed; Perveen, Rawshan Ara; Akhtar, Afzal; Rahman, A. F. M. Mohibur; Farha, Nadia; Chowdhury, A. S. M. Salauddin (International Journal of Advances in Medicine, 2021)
Background: The first recognition of a cluster of COVID-19 patients in China in late 2019, has become a major concern due to its greater transmissibility and vulnerability of the patient to turn to fever, cough, breathlessness, pneumonia then eventually severe acute respiratory distress syndrome requiring intensive care unit (ICU) support. But most of the affected patients get cured following mild symptoms and very only a few of them get hospitalized. The objective of the study was to observe the demographic characteristics, clinical symptoms, comorbidities, and biomarkers (hematological, inflammatory, hepatic, renal, and metabolic) of mild cases of COVID-19 infected patients admitted to the hospital during the peak four months of the pandemic. Methods: Age, sex, symptoms, comorbidities, and biomarkers (Hb%, WBC, lymphocyte, neutrophil, platelet count, HCT(hematocrit), NLR(neutrophil-lymphocyte ratio, d-NLR derived neutrophil-lymphocyte ratio, PLR(platelet-lymphocyte-ratio), d-Dimer, ferritin, CRP(C-reactive protein), PT(prothrombin time), INR(international normalized ratio), SGPT, S.creatinine, HbA1C of all rt-PCR positive mild cases were recorded in this retrospective observational study in a tertiary care hospital dedicated to COVID-19 at Dhaka, Bangladesh was done from 15th May to 9th September, 2020. Age, sex, symptoms, and comorbidities were compared by chi-square test and biomarkers were compared by one-way ANOVA. Results: Out of 254 cases 44 were female and 210 were male with a ratio of 1:4.77. Average age was 39.04. Largest population belongs to the 30-39 years of age range. Among the symptoms, anorexia (18.5%), fever (17.71%), and anosmia (16.9%) were most prevalent symptoms among the mild cases. However, diabetes mellitus (DM) and hypertension (HTN) were predominant comorbidities. Mostly all the biomarkers were significant among groups (Hb%, Total WBC, neutrophil count, platelet count, HCT, NLR, d-NLR, d-Dimer, ferritin, CRP, PT, SGPT, creatinine, HbA1C except lymphocyte count, PLR, and INR. The severity of disease progression depends on the co-morbidity and hyper-responsiveness inflammatory or immunological biomarkers to predict. Conclusions: In mild cases of COVID-19 male predominance was more and the most affected group was 30-39 years. They suffered more from anorexia and fever and DM and HTN were common comorbidities. Mostly all the biomarkers were significant. Moreover, further large-scale studies are needed to evaluate the number of mild cases and their prognostic features to develop and modify the treatment strategy and public health awareness time to time.